2015
DOI: 10.1155/2015/968582
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Distribution of Archaea in the Mangrove Sediment of Sundarbans

Abstract: Mangroves are among the most diverse and productive coastal ecosystems in the tropical and subtropical regions. Environmental conditions particular to this biome make mangroves hotspots for microbial diversity, and the resident microbial communities play essential roles in maintenance of the ecosystem. Recently, there has been increasing interest to understand the composition and contribution of microorganisms in mangroves. In the present study, we have analyzed the diversity and distribution of archaea in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 56 publications
(50 reference statements)
2
29
1
Order By: Relevance
“…In previous researches, Crenarchaeota and Euryarchaeota were always detected with high abundance in mangrove sediment ecosystems (Yan et al 2006;Mendes et al 2012;Pires et al 2012;Chen et al 2013;Silveira et al 2013;Otero et al 2014), and low abundance of Thaumarchaeota was found in some studies (Mendes et al 2012;Pires et al 2012;Silveira et al 2013;Otero et al 2014). One study in three mangrove sediments under different stages of preservation reported Archaea groups of Thaumarchaeota (53.21 %), Euryarchaeota (29.6 %), and unclassified Archaea (16.1 %), but no Crenarchaeota (Dias et al 2011); another study from mangrove sediment of Sundarbans revealed the dominance of Euryarchaeota and Thaumarchaeota (Bhattacharyya et al 2015), which was consistent with Dias et al (2011). In terms of the abundance of Crenarchaeota and Euryarchaeota, our result in the K. candel, L. racemosa, S. apetala, and B. gymnoihiza stands was in agreement with some researches that Euryarchaeota had a greater abundance than Crenarchaeota in mangrove sediment ecosystems (Mendes et al 2012;Chen et al 2013) (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous researches, Crenarchaeota and Euryarchaeota were always detected with high abundance in mangrove sediment ecosystems (Yan et al 2006;Mendes et al 2012;Pires et al 2012;Chen et al 2013;Silveira et al 2013;Otero et al 2014), and low abundance of Thaumarchaeota was found in some studies (Mendes et al 2012;Pires et al 2012;Silveira et al 2013;Otero et al 2014). One study in three mangrove sediments under different stages of preservation reported Archaea groups of Thaumarchaeota (53.21 %), Euryarchaeota (29.6 %), and unclassified Archaea (16.1 %), but no Crenarchaeota (Dias et al 2011); another study from mangrove sediment of Sundarbans revealed the dominance of Euryarchaeota and Thaumarchaeota (Bhattacharyya et al 2015), which was consistent with Dias et al (2011). In terms of the abundance of Crenarchaeota and Euryarchaeota, our result in the K. candel, L. racemosa, S. apetala, and B. gymnoihiza stands was in agreement with some researches that Euryarchaeota had a greater abundance than Crenarchaeota in mangrove sediment ecosystems (Mendes et al 2012;Chen et al 2013) (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Mangroves provide a unique ecological environment for diverse microbial communities (Kathiresan and Bingham 2001), including Archaea, the third domain of life that are often found in a wide range of environments (Chaban et al 2006). To date, studies focused on Archaea in mangrove ecosystems have dealt mainly with archaeal communities (Yan et al 2006;Rooney-Varga et al 2007;Pires 2010;Mendes et al 2012;Pires et al 2012;Tian et al 2012;Bhattacharyya et al 2015), methanogenic archaea (Mohanraju and Natarajan 1992;Lyimo et al 2000;Lyimo et al 2009;Taketani et al 2010), and ammoniaoxidizing archaea (Li et al 2011;Li and Gu 2013;Wang et al 2013;Wang and Gu 2014), but it still remains unclear whether there are differences in the composition, structure, and diversity of the archaeal communities in the sediments of different mangrove species.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to bacteria, the diversity and community distribution of sediment archaea have received much less attention in freshwater lake environments. Few previous studies indicated the variation of archaea community structure and diversity with several factors, such as sediment depth, sampling sites, and contamination [1012]. Archaea community is less influenced by environmental factors compared with bacteria [13]; several parameters are found to affect the distribution of archaea in lake sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove forests provide a unique ecological environment for diverse microbial communities [3], including archaea, which plays an important role in greenhouse gas production from natural wetland. A large number of studies have investigated the composition of archaea communities in different mangrove forest sediments [4][5][6][7][8][9][10][11][12][13]. Mangrove sediment archaeal community patterns were influenced by environmental conditions [5], and studies in mangrove forests also revealed that pH was the most influential factor in shaping the archaeal communities [14].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have investigated the composition of archaea communities in different mangrove forest sediments [4][5][6][7][8][9][10][11][12][13]. Mangrove sediment archaeal community patterns were influenced by environmental conditions [5], and studies in mangrove forests also revealed that pH was the most influential factor in shaping the archaeal communities [14]. However, mangrove forest sediment is a high salinity environment with salt and fresh water from periodic tides and rivers, and few studies have reported the archaea communities and diversity in sediments of mangrove forest distribution areas with salinity gradients.…”
Section: Introductionmentioning
confidence: 99%